Effect of Talent Development on Employees Performance; A Case Study of Benue State University, Makurdi (Global Journal of Management and Business Research, 2022)
This study examines effect of Talent development on employees performance. The study focus on Benue State University Makurdi. The study specifically examines the effect of career development, coaching and mentoring in Benue state University. The study adopted survey design and questionnaire was used as an instrument for data collection .The population of the study consists of 1,974 staff. Multiple regression was used as a technique of data analysis. Findings of the study revealed that, career development, coaching and mentoring significantly influenced employees performance at Benue state University. The study recommended that, Management of Benue State University Makurdi should ensured that programmes are designed for academic and non academic staff of the institution to enhanced staff career development and adequate measures should be implemented for coaching and mentoring of young talented academic and non academic staff of the institution.